Adverse event profile of lorazepam: a real-world pharmacovigilance study using the FDA adverse event reporting system database - Zhengkang Su; Zhengwei Huang; Xiaoyu Chen; Xiaoyu Chen; Xi Li (Frontiers Media S.A., 2024)
IntroductionAnxiety diagnoses have surged recently during and after the COVID-19 pandemic. Lorazepam is widely recognized for its efficacy in treatment of anxiety, as well as insomnia, etc. However, the long-term safety profile of lorazepam in extensive patient populations has not been thoroughly established.MethodsThis study aims to evaluate the potential lorazepam-associated adverse events (AEs) using data mining of the Food and Drug Administration Adverse Event Reporting System (FAERS) of the United States, seeking to provide a guidance for the future therapeutic practices.ResultsOur study revealed drug abuse, suicide attempt, sopor, delirium, and psychotic disorder were among the most prevalent AEs linked to lorazepam. In addition to common AEs, we also found that patients using lorazepam may have the risk of abnormal fat metabolism, cardiac impairment, and immunosuppression-related disorders.DiscussionIn general, our research has unveiled novel AE signals and expanded our understanding of the safety profile of lorazepam in clinical practices, providing guidance for its rational use.